Impacts of Rural Electrification in Rwanda - Gunther Bensch; Jochen Kluve; Jörg Peters (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
Rural electrification is believed to contribute to the achievement of the MDG. In this paper, we investigate electrification impacts on different indicators. We use household data that we collected in Rwanda in villages with and without electricity access. We account for self-selection and regional differences by using households from the electrified villages to estimate the probability to connect for all households - including those in the non-electrified villages. Based on these probabilities we identify counterfactual households and find robust evidence for positive effects on lighting usage. Effects on income and children's home studying become insignificant if regional differences are accounted for.
Keywords: O12; O13; O18; O22; 330; Rural electrification; energy access; impact evaluation; matching